The Ascent of Educational Psychology in Denmark in the Interwar Years - Hamre, Bjørn; Ydesen, Christian (Nordic Journal of Educational History, 2014)
In this article, we argue that an understanding of the interwar years and the ascent of educational psychology contribute valuable knowledge about the inner workings of modern-day education with regard to the links between society and education in general and the boundary between normality and deviation in particular. The establishment of the educational psychologist’s office at Frederiksberg in Denmark, the introduction of IQ testing, and the related psychological files of students provide an image of a period of measurement in schools during which IQ testing was decisive in decisions to transfer students to the remedial school. The testing and filing were the foremost important technologies of the period. We draw on sources that allow us to view educational psychology and testing in their local, national, and political context. The sources applied are primarily obtained from Frederiksberg City Archive that contains archives from the Educational Psychology Office.